Collective action, property rights, and devolution of natural resource management: exchange of knowledge and implications for policy - Knox, Anna; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2000)
Policies to devolve responsibility for natural resource management to local bodies have become widespread in the past 20 years. Although the theoretical advantages of user management have been convincing and the impetus for devolution policies strong, the actual outcomes of devolution programs in various sectors and countries have been mixed. This paper summarizes key research findings on factors that contribute to effective devolution programs in the forestry, fisheries, irrigation, and rangelands sectors, which were presented and discussed at an international Policy Workshop on Property Rights, Collective Action and Devolution of Natural Resource Management, June 21-25, 1999, in Puerto Azul, the Philippines. We begin by addressing the language of devolution in an effort to clarify concepts and terminology that enable a more productive discussion of the issues. This is followed by some of the key arguments made by the workshop participants for devolving rights to resources to local users. Policies and factors that have the potential to strengthen or constrain devolution are addressed at a broad level before looking specifically at how property rights and collective action institutions can shape devolution outcomes. Whereas some factors cut across resource sectors and regions, others are more specific to their contexts. In all cases, proponents of devolution of rights to resource users struggle to understand better what elements facilitate collective action and what factors hinder its creation and sustainability. Finally, a set of recommended frameworks formulated by the workshop participants highlight the potential for fostering a devolution process that leads to the simultaneous improvement of natural resource management and the livelihoods of the poor.